First person - Jenny Vermeer and Jonathan lent (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Jenny Vermeer and Jonathan lent are co-first authors on 'A lineage-tracing tool to map the fate of hypoxic tumour cells', published in DMM. Jenny conducted the research described in this article while a postdoctoral researcher in the lab of Ruth Muschel at the University of Oxford, Oxford, UK. She is now a project leader in the lab of Miranda van der Lee at Byondis, Nijmegen, The Netherlands, investigating new targets, particularly in cancer, that will lead to novel treatments. Jonathan is a PhD student in the lab of Marc Vooijs at Maastricht University, Maastricht, The Netherlands, investigating new cancer targets and testing possible new interventions with a focus on tumour hypoxia.